Analysis of the most suitable period for the mapping of the land-tenures from the satellite multispectral images - Bujauskas, Arūnas; Paršeliūnas, Eimuntas (Geodesy and Cartography, 2012)
Satellite multispectral images data is now a key source for spatially distributed land cover information, which is increasingly available in digital format for use in Geographic Information Systems (GIS). Remote sensing and GIS have become the most suitable technology of obtaining the required land cover data with high temporal and spatial accuracy. The land-tenures classes could be detected using satellite multispectral images from Landsat 5 and 7 satellites. Due to complicated meteorological conditions over Lithuanian territory the satellite multispectral images often are not of good quality. That influences the final quality of the land-tenure identification and mapping. Analysis of the most suitable period for the satellite multispectral images acquisition for the Lithuanian territory is presented. Article in Lithuanian. Laikotarpio tinkamumo kartografuoti Žemės naudmenas pagal palydovines daugiaspektres nuotraukas analizė Santrauka. Straipsnyje analizuojama, kuriuo žemės paviršiaus distancinių tyrimų laikotarpiu tinkamiausia kartografuoti žemės naudmenas. Žemės naudmenoms kartografuoti taikomos LANDSAT 5 ir LANDSAT 7 palydovais gautos daugiaspektrės nuotraukos, o laikotarpiai parenkami pagal šių palydovų skridimo virš Lietuvos teritorijos grafikus. Dėl Lietuvos teritorijos klimatinių s ąlygų sudėtingumo daugiaspektrės nuotraukos dažnai gaunamos nepakankamai kokybiškos, o tai sumažina tikimybę turėti tinkamus duomenis analizei ir kartografavimui. Prasminiai žodžiai: nuotoliniai tyrimai, žemės naudmenos, skenavimo laikotarpis, palydovas LANDSAT, daugiaspektrė nuotrauka. First published online: 03 Aug 2012